2007
DOI: 10.1002/jcop.20155
|View full text |Cite
|
Sign up to set email alerts
|

How settings change people: Applying behavior setting theory to consumer‐run organizations

Abstract: Self-help initiatives stand as a classic context for organizational studies inCommunity psychologists have long been interested in understanding self-help initiatives such as consumer-run organizations (CROs). As cost-effective resources that are currently expanding their influence in the community, CROs stand to have a major impact on the treatment of mental illness. These organizations embody much of what community

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
(39 reference statements)
2
18
0
1
Order By: Relevance
“…These processes are consistent with expectations of the ''helper/therapy principle'' (Brown et al, 2007) and related theorizing by Nelson et al (2006) about the ''power reversal'' process and by Mead et al (2001) about the importance of managing conflict and developing shared responsibility. Our research involved an intensive investigation of these processes.…”
Section: Social Isolation and Peer Supportsupporting
confidence: 67%
See 2 more Smart Citations
“…These processes are consistent with expectations of the ''helper/therapy principle'' (Brown et al, 2007) and related theorizing by Nelson et al (2006) about the ''power reversal'' process and by Mead et al (2001) about the importance of managing conflict and developing shared responsibility. Our research involved an intensive investigation of these processes.…”
Section: Social Isolation and Peer Supportsupporting
confidence: 67%
“…Brown et al (2007) found benefits of participation in consumer-run organizations based on retrospective self-report. Based on crosssectional research, Davidson et al (1999) reported greater social integration among mutual support participants: more voluntary relations, more valued social roles, and more life-enriching activities.…”
Section: Social Isolation and Peer Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Just like the 'social movement service organizations' conceptualized by Meyer (2010), many organizations are hybrid in activity. In these organizations, service provision and advocacy are intimately linked core activities where advocacy is seen as related to personal gain and service provisioning as empowering and political (Brown et al 2007b;Stylianos and Kehyayan 2012;Tanenbaum 2011). Gee et al (2015) as well as Janzen et al (2006) describe how MHSUO representatives are frequently invited to participate in policy development and community planning which currently constitute the core activities of many organizations.…”
Section: Hybridization Of Activitiesmentioning
confidence: 99%
“…En effet, des pairs aidants sont payés pour aider des usagers qui ne sont pas eux-mêmes considérés comme pairs aidants. Néanmoins, plusieurs études ont lié l'acquisition d'un sentiment de contrôle et de responsabilisation à la fréquentation de centres autogérés par des pairs aidants (par exempleBrown, Shepherd, Wituk & Meissen, 2007 ;Chamberlin, Rogers & Ellison, 1996). Mowbray et Tan (1993) ont conclu que la fréquentation de centres de jour (drop-in centers) autogérés par des pairs aidants a induit, chez plus de la moitié de ceux qui les ont fréquentés (53 %), une plus grande confiance dans leurs décisions concernant leur emploi, leur éducation, leurs relations interpersonnelles et leur traitement.…”
Section: ) Les Services Gérés Par Des Pairs Aidantsunclassified